2023
DOI: 10.1163/1568539x-bja10210
|View full text |Cite
|
Sign up to set email alerts
|

Ring a bell? Variable recognition of a multicomponent auditory stimulus associated with predation risk by zebrafish responding to full and partial matches

Abstract: Many fishes learn to recognize correlates of predation risk by pairing novel stimuli with injury-released chemical cues released from damaged epidermal tissues. Here, zebrafish were conditioned to associate predation risk with a three-note auditory stimulus C5 (523.25 Hz) + E5 (659.25 Hz) + G5 (783.99 Hz), then tested for responses to either only one tone (C), two of the components (C + G) or the full three-note chord (C + E + G). Zebrafish conditioned with alarm cues and C + E + G responded significantly more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Recently it has been demonstrated that some fish can associate risk with auditory stimuli when a novel auditory stimulus is paired with chemical alarm cues released from damaged epidermis (e.g., Johnson et al, 2023;Seigel et al, 2021Seigel et al, , 2022Wisenden et al, 2008). Fathead minnows Pimephales promelas and glowlight tetras Hemigrammus erythrozonus learn to associate risk with a tone when the tone and conspecific alarm cues from damaged skin of conspecifics are presented simultaneously (Wisenden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been demonstrated that some fish can associate risk with auditory stimuli when a novel auditory stimulus is paired with chemical alarm cues released from damaged epidermis (e.g., Johnson et al, 2023;Seigel et al, 2021Seigel et al, , 2022Wisenden et al, 2008). Fathead minnows Pimephales promelas and glowlight tetras Hemigrammus erythrozonus learn to associate risk with a tone when the tone and conspecific alarm cues from damaged skin of conspecifics are presented simultaneously (Wisenden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%